METALANGUAGE AS PEDAGOGICAL PHENOMENON AND ITS ROLE IN LANGUAGE DEVELOPMENT OF PERSONALITY AT SCHOOL - Yelena N. Volodina (Образование и наука)
The aim of this article is to consider psychological and pedagogical mechanisms of personal language development and formation of humanitarian culture of schoolchildren as part of their general culture by means of language as a symbolic and cultural phenomenon.Methods. Theoretical analysis, synthesis, generalization, specification, comparison, classification are the methods applied in this research. Conclusions are made on the basis of contemporary socio-cultural and linguistic situation analysis of fundamental psycho-pedagogical and linguistic theories and generalization of experience of the network project «Language personality development in the system of general education at schools of the Tyumen region».Results. It is proved that effective language education in the context of contemporary socio-cultural situation and new educational standard requirements is possible on the basis of updating axiological humanitarian approaches, which are linguistic and culturological, semiotic, hermeneutic; and help to design the metalanguage educational space as a space of intersection of different languages, subject-specific and interdisciplinary, cognitive and linguistic pictures of the world, between different speech practices. The article considers the nature and content of the metalanguage, based on mental corpus of individuals, including cultural, linguistic, semiotic concepts, metaphorical layer of language, cognitive metaphors, idioms, phraseological units, etc. It is proved that reading and understanding of text, its analysis and personal interpretation, production of «secondary» and «counter» texts are the main types of metalanguage activities in the process of general personality development, when metalanguage is a mechanism of conceptualization of individual consciousness, the formation of individual linguistic picture of the world and individual concept sphere, enrichment of personal worldviews and sensitive experience, and value development of metatext of culture.Scientific novelty. The article reveals the author’s concept of language development and metalanguage as a pedagogical phenomenon, which in the educational semiotics is systemic. The concept of metalanguage, which is a universal language, the language of culture is a broad way to build meta-scientific concepts, a tool of mastering all subject areas and different «subject» languages at school.Practical significance. The materials provided in this article will help teachers, heads of educational institutions in the implementation of new language policies and organization of the process of language development of personality based on humanitarian approaches.